Salmonella Control Programme of Pig Feeds Is Financially Beneficial in Finland - Niemi, Jarkko K.; Heinola, Katriina; Simola, Maria; Tuominen, Pirkko (Frontiers in Veterinary Science, 2019)
To promote public health, Finland has adopted a stringent Salmonella control policy. However, the rationale of Salmonella control in pig feeds has been debated after an EU-wide cost-benefit analysis which provided mixed, country-specific results on whether control measures are economically beneficial. The aim of this study was to analyse the costs and benefits of current pig feed Salmonella control in Finland compared to a reduced control scenario. In addition, this study contributes to the literature by looking at the costs across stakeholder groups. The costs of preventive and monitoring measures were assessed and a Monte Carlo model was developed to simulate costs caused by Salmonella contaminations along the pork supply chain (including feed importation, commercial feed manufacturing, feed transportation, mobile feed mixers, pig farms, slaughterhouses) and because of human salmonellosis originating from contaminated feed. The data were collected from official records and feed sector operators by surveys and interviews. The prevalence of Salmonella was obtained from a previously conducted risk assessment study. The total costs of pig feed Salmonella control were estimated on average to be €4.2 – 5.4 million per year (95% of simulated years between €2.1 and €9.1 million) for the current control scenario, and €33.8 – €34.8 million per year (95% €2.2 to €26.0 million) for the reduced control scenario. In the reduced control scenario the monitoring and prevention costs were decreased down to €1.1 – 2.1 million and the costs of Salmonella contaminations and human salmonellosis were up by €32.7 million when compared to the current control scenario. The results suggest that the current pig feed Salmonella control policy of Finland is economically profitable. It can reduce the costs caused by feed-related Salmonella contaminations on average by €29.4 million per year and provides public health benefits. Pig feed Salmonella control can support the effectiveness of Finnish Salmonella Control Programme. The current pig feed Salmonella control policy benefits the consumers, while a substantial part of the costs are covered by feed operators. In order to increase the acceptability of current policy, greater attention to the allocation of financial responsibilities regarding the control measures may be required.